2021
DOI: 10.5469/neuroint.2021.00241
|View full text |Cite
|
Sign up to set email alerts
|

PulseRider Treated Aneurysm with Significant Artifact on Postoperative Magnetic Resonance Angiography: A Case Report and Literature Review

Abstract: The PulseRider is a neuroendovascular adjunct for wide-necked intracranial aneurysms. The decreased metal burden of the PulseRider theoretically reduces artifact on radiologic imaging. However, we report here on a case of a patient who underwent PulseRider-assisted stent-coiling of a basilar tip aneurysm. He returned 19 months later for intermittent diplopia and darkening of vision but was neurologically intact on exam. Both contrast-enhanced and time-of-flight magnetic resonance angiography (MRA) demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…A segment of the proximal marker portion was poorly visualized even in silent MRA. Nguyen et al reported that this is due to metal artifacts made of stainless steel at the detachment points [ 11 ]. Stainless steel causes more susceptibility artifacts than other metal components such as nitinol and platinum [ 12 ], and it hinders the evaluation of flow signal in segmental parent arteries even in silent MRA.…”
Section: Discussionmentioning
confidence: 99%
“…A segment of the proximal marker portion was poorly visualized even in silent MRA. Nguyen et al reported that this is due to metal artifacts made of stainless steel at the detachment points [ 11 ]. Stainless steel causes more susceptibility artifacts than other metal components such as nitinol and platinum [ 12 ], and it hinders the evaluation of flow signal in segmental parent arteries even in silent MRA.…”
Section: Discussionmentioning
confidence: 99%